Penerapan Game untuk Belajar Matematika Menyenangkan di Panti Asuhan Al-Khaerat Makassar - ., Indrabayu; Warni, Elly; Nurtanio, Ingrid; Yohannes, Chystoporus; Alimuddin, A.Ais Prayogi; Bustamin, Anugrahyani; Areni, Intan Sari; Muslimin, Zaenab; Yusuf, Mukarramah; Mokobombang, Novy Nur R.A; Nurdin, Winati Mutmainnah; Anisah, Siti Nur (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2023)
Mathematics is one of the important subjects in the educational curriculum, but it is often considered difficult and boring by some children. This can be an obstacle in their learning process and academic development. Therefore, in an effort to help increase interest and achievement in learning mathematics and develop children's potential and talents, we as a service team from the Department of Informatics Engineering, Faculty of Engineering, Hasanuddin University feel the need to contribute by holding mathematics game socialization activities at Al-Khaerat Makassar Orphanage. The community service carried out at the Al-Khaerat Makassar Orphanage aims to provide new insights for students related to digital learning methods and materials within the scope of mathematics learning with a fun and interactive approach, it is hoped that students can feel more interested and enthusiastic in learning mathematics. The implementation of community service is divided into two stages, namely the socialization stage of learning methods by utilizing technology, in this case smartphones and the training stage of using mathematical educational game applications. The results of the analysis through pre-test and post-test questionnaires show that the use of the Mathology Game application has a significant impact on students mathematics learning in three main aspects, namely: comfort, easy, and understanding of the material.